Studies on Environmental Friendlier Magnesium Fuel from Liquid Waste Bittern - Shalaby, M. S.; El-Sherbini, Shakinaz A.; Ramadan, Rania; El-Rafie, Shadia A.; Sibak, Hanem A. (Advanced Aspects of Engineering Research Vol. 13, 2021)
Magnesium metal production is expected to rise substantially over the next decade and beyond, owing to a perceived need to curb fossil fuel consumption while also lowering greenhouse gas emissions. Bittern is regarded as a hazardous liquid waste to the atmosphere, causing significant environmental issues; however, it has many applications in manufacturing and agriculture, as well as being used in the manufacture of magnesium and other chemicals. Precipitation methods using sodium or ammonium hydroxide or oxalic acid solutions were proposed to extract pure magnesium oxide from bittern, and technology processes incorporating both were proposed. Magnesium metal manufacturing is technically challenging, as well as having extremely high production costs. Latest methods of producing magnesium metal from oxides include high-temperature reduction, electrolysis of molten magnesium chloride, and other methods involving the use of a laser and solar energy. The bittern solution represents a typical valuable resource for magnesium and other economical salts which could be produced as by- products in the processing of Magnesia.